The Labial Adhesion in Postmenopausal Women: A Systematic Review - Nastaran Mahmoudnejad; Mohammad Hamidi Madani; Roozbeh Roohinezhad (Iranian Journal of Medical Sciences)
Background: Labial adhesion (LA) is a total or partial labial fusion mostly seen in pre-pubertal children and is rare in premenopausal and postmenopausal periods. This review aimed to evaluate risk factors for labial fusion and the recurrence rate following surgical intervention in postmenopausal women.Methods: According to PRISMA guidelines, international databases including Embase, World Cat, Web of Science, Scopus, Dimension, Open Grey, Cochrane, Google Scholar, and also PubMed gateway for PMC and MEDLINE were searched. The included studies were in English and published from 1985 until December 2023 with the keywords including vulvar diseases, agglutination, menopause, postmenopause, and recurrence. All studies that evaluated the clinical course and recurrence of LAs following surgical treatment in postmenopausal women were included. The inclusion criteria were the risk factors of LA recurrence rate, and the exclusion criteria were studies with missing required data, letters to editors, and conference studies.Results: Thirty-four case reports were enrolled. In total, 54 patients were evaluated. The most common risk factors for LA included hypoestrogenism, virginity, sexual inactivity, cervical cancer, hysterectomy, urinary tract infections, and lichen sclerosis. Only one study reported a recurrence of labial fusion following surgical intervention in a one-year follow-up.Conclusion: The most common risk factors for LA were hypoestrogenism, virginity, sexual inactivity, cervical cancer, hysterectomy, urinary tract infections, and lichen sclerosis. The low recurrence rate following surgical release of labial fusion has made it an effective and safe method in postmenopausal women with negligible medium-term recurrence rates.